Rituximab, a Safer Option for Rheumatoid Arthritis: A Comparison of the Reported Adverse Events of Approved Monoclonal Antibodies. Issue 4 (December 2022) - Sharma, Sweety; Basu, Somnath; Goyal, Ramesh K.; Sahoo, Parbhat K.; Mathur, Rajani
Monoclonal antibodies (mAbs), which are commonly used to treat rheumatoid arthritis (RA), have been linked to a variety of adverse events (AEs). The objective of the study was to compare the safety profiles of six FDA approved mAbs (sarilumab, tocilizumab, adalimumab, golimumab, infliximab, and rituximab) marketed for the treatment of RA. A systematic review of the literature was conducted using the databases PubMed, Cochrane Library, and Science Direct. The manuscript comprised a total of 23 clinical studies. The percentage of patients who had AEs was calculated and presented using box-whisker and forest plots. Infections and infestations were found to be the most common AEs in RA patients treated with mAbs. Raised alanine aminotransferase (ALT), aspartate aminotransferase (AST), upper respiratory tract infection (URTI), and nasopharyngitis were frequently reported. The most common AEs were reported with adalimumab. The highest percentage of patients reporting AEs was associated with golimumab (52%), while rituximab had the fewest AEs (4.9%). In conclusion, rituximab appears to be a safer treatment option for RA as it is found to be associated with a lower risk of AEs, particularly respiratory infections.